Analyzing effectiveness of active learning through project-based learning approach in university level ICT courses - Shrestha, Dhiraj; Lohani, Satyendra Nath; Adhikari, Roshan Manjushree (Journal of Engineering Issues and Solutions, 2021)
The concept of Active Learning (AL), which has journeyed through multiple research studies over the years, is an important part of the teaching learning process at academic institutions. The present study applies active learning via project-based approaches where students engage in real life projects and solve associated complications with their research, communication, and technical skills. As a case study of effectiveness of project-based learning (PBL), especially in engineering project contexts, the present research is conducted among students studying computer science and engineering at Kathmandu University (KU), Nepal. The key findings of the study suggest that PBL assignments have helped students in their active learning processes. This paper also compares teaching and learning approaches of KU with other IT institutions of Nepal.